2018
DOI: 10.1002/hpm.2657
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of advanced medical imaging technology, CT, and MRI scanners, in Iran: A qualitative study of determinants

Abstract: SummaryBackgroundLow‐income and middle‐income countries have a lot of problems in providing the financial, human, and capital resources for advanced medical imaging technologies (AMITs). Proper distribution of such expensive equipment might increase access to these services and enhance the quality and efficiency of health care. The present study aimed to identify the factors affecting the diffusion of AMITs including CT and MRI in Iran.MethodsThis is a qualitative research conducted in 2017. A number of purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In line with this, Harstall [ 29 ] reported that hospital size, teaching role, greater specialization, research activity and resource availability were positively associated with technology adoption. In turn, Abedini et al [ 30 ] concluded that the main factors influencing CT and MRI adoption were the number of beds, doctors and patients and hospital location, whereas Hong [ 31 ] showed that the number of CT units reflected bed and specialty numbers and, most especially, location in larger cities. Finally, Hall [ 32 ] found that greater use of diagnostic technologies was associated with greater population density, more doctors per capita, a higher ratio of specialists to general practitioners and a higher percentage of doctors involved in teaching.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Harstall [ 29 ] reported that hospital size, teaching role, greater specialization, research activity and resource availability were positively associated with technology adoption. In turn, Abedini et al [ 30 ] concluded that the main factors influencing CT and MRI adoption were the number of beds, doctors and patients and hospital location, whereas Hong [ 31 ] showed that the number of CT units reflected bed and specialty numbers and, most especially, location in larger cities. Finally, Hall [ 32 ] found that greater use of diagnostic technologies was associated with greater population density, more doctors per capita, a higher ratio of specialists to general practitioners and a higher percentage of doctors involved in teaching.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the CTC group spent approximately 50% less time undergoing imaging than the control group ( Figure 3B). While traditional imaging (DUS, CT and MRI) remains indispensable for followup of cancer patients, 32 specialists and expensive equipment are needed to perform CT and MRI. 33 Therefore, the price of imaging examination only decreased by approximately 15%, and there is limited opportunity for further price decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian guidelines are mostly concordant with the WHO recommendations for primary screening of suspected cases by RT-qPCR [ 127 ], as well as India [ 8 ], Brazil [ 128 ], Portugal [ 129 ], and China [ 130 ]. However, in Iran, a shortage of RT-qPCR testing kits led local medical authorities to establish an imaging-driven screening system, with chest CT representing the first-line diagnostic modality [ 131 ], even though there were only 6.5 CT scanners per million population [ 132 ]. The shortage of RT-qPCR kits has not only been reported in middle-income countries but also in certain states of the United States at times when there were peaks in the number of COVID-19 cases [ 133 ].…”
Section: Nucleic Acid-based Testsmentioning
confidence: 99%